Amount and delay insensitivity during intertemporal choice in three neurodegenerative diseases reflects dorsomedial prefrontal atrophy. (March 2020) - Beagle, Alexander J.; Zahir, Ali; Borzello, Mia; Kayser, Andrew S.; Hsu, Ming; Miller, Bruce L.; Kramer, Joel H.; Chiong, Winston
Abstract: Patients with Alzheimer's disease and other dementias often make poor financial decisions, but it remains unclear whether this reflects specific failures in decision-making or more general deficits in episodic and working memory. We investigated how patients with Alzheimer's disease, behavioral variant frontotemporal dementia (bvFTD), and semantic variant primary progressive aphasia (svPPA) apply information in an intertemporal choice task between smaller intermediate and larger delayed rewards, with minimal memory demands. Multilevel modeling estimated subject-level sensitivities to three attributes of choice (the relative difference in reward magnitude, delay length, and absolute reward magnitudes) as well as baseline impulsivity. While baseline impulsivity in patients with Alzheimer's disease did not differ from controls, patients with bvFTD and svPPA were more impulsive than controls overall. Patients with Alzheimer's disease or bvFTD were less sensitive than controls to all three choice attributes, whereas patients with svPPA were less sensitive than controls to two attributes. Attenuated sensitivity to information presented during the choice was associated across all subjects with dorsomedial prefrontal atrophy for all three choice attributes. Given the minimal memory demands of our task, these findings suggest specific mechanisms underlying decision-making failures beyond episodic and working memory deficits in dementia.